STRATEGI DESAIN DALAM MENGHIDUPKAN KEBUDAYAAN BETAWI - Rebecca Cendra; Rudy Trisno (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
The rampant developments in the capital city seem to be a disaster that has eroded Betawi culture. Many Betawi people have had to let go of their land and move to the outskirts of Jakarta. Without realizing it, this turned out to have caused the Betawi arts and traditions to fade away. Therefore, this study aims to determine architectural design strategies that can maintain the existence of Betawi culture. The method used is qualitative with data collection techniques through observation of secondary data. The data obtained were then analyzed descriptively using indicators: 1) Location suitability; 2) The mass layout pattern of buildings and spaces according to the locality; 3) Materials that reflect locality; 4) The shape and visual of the building considering the locality; and 5) Space program that is able to accommodate the demands of needs and accommodate cultural activities. The results of the research show that the way to maintain the existence of Betawi culture is not just providing a cultural platform, but also empowering the community so that their economy and welfare are maintained. Keywords: architecture; betawi; culture; economy; locality Abstrak Pembangunan yang marak terjadi di Ibu Kota seakan menjadi bencana yang menggerus kebudayaan Betawi. Banyak masyarakat Betawi yang harus mengikhlaskan lahannya dan pindah ke pinggir kota Jakarta. Tanpa disadari, hal ini ternyata menyebabkan tradisi dan kesenian Betawi semakin memudar. Maka dari itu, penelitian ini bertujuan untuk mengetahui strategi perancangan arsitektur yang dapat mempertahankan eksistensi kebudayaan Betawi. Metode yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui observasi dari data sekunder. Data yang diperoleh kemudian dianalisis secara deskriptif menggunakan indikator: 1) Kesesuaian lokasi; 2) Pola tata massa bangunan dan ruang yang sesuai dengan lokalitas; 3) Material yang mencerminkan lokalitas; 4) Bentuk dan visual bangunan yangmempertimbangkan lokalitas; serta 5) Program ruang yang mampu mewadahi tuntutan kebutuhan dan mewadahi aktivitas kebudayaan. Hasil penelitian menunjukan bahwa cara untuk mempertahankan eksistensi budaya Betawi bukan hanya sekadar menyediakan wadah kebudayaan saja, tetapi juga melakukan pemberdayaan terhadap masyarakatnya agar perekonomian dan kesejahteraan mereka tetap terjaga.